2015
DOI: 10.1128/aac.03543-14
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dengue Virus NS2B/NS3 Protease Inhibitors

Abstract: Dengue fever is a severe, widespread, and neglected disease with more than 2 million diagnosed infections per year. The dengue virus NS2B/NS3 protease (PR) represents a prime target for rational drug design. At the moment, there are no clinical PR inhibitors (PIs) available. We have identified diaryl (thio)ethers as candidates for a novel class of PIs. Here, we report the selective and noncompetitive inhibition of the serotype 2 and 3 dengue virus PR in vitro and in cells by benzothiazole derivatives exhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 36 publications
(37 reference statements)
7
107
0
2
Order By: Relevance
“…There are globally known four antigenically distinct serotypes (DENV 1, 2, 3, and 4) exist, and they are mostly prevalent in dengue‐endemic regions such as Asia, Africa, and America . All these serotypes share more than 70% sequence homology with GC conservation regions, and infections caused by these serotypes also share common dengue viral symptoms .…”
Section: Introductionmentioning
confidence: 99%
“…There are globally known four antigenically distinct serotypes (DENV 1, 2, 3, and 4) exist, and they are mostly prevalent in dengue‐endemic regions such as Asia, Africa, and America . All these serotypes share more than 70% sequence homology with GC conservation regions, and infections caused by these serotypes also share common dengue viral symptoms .…”
Section: Introductionmentioning
confidence: 99%
“…These efforts have resulted in identification of a variety of small molecules that inhibit viral replication through targeting distinct viral and host cellular functions (17)(18)(19). Small molecules that specifically target viral capsid assembly (20), NS3/2A proteases (21)(22)(23), NS3 RNA helicase (24), NS4B protein (25,26), NS5 methyltransferase (27), and RNA-dependent RNA polymerase (28,29) have been discovered, and the in vivo antiviral efficacies for four of these direct-acting antiviral (DAA) agents have been demonstrated in animal models (24,(30)(31)(32); however, none of them has reached human clinical trials. Balapiravir, a tri-isobutyrate ester prodrug of 4=-azidocytidine (R1479) that was originally developed for treatment of chronic hepatitis C virus (HCV) infection by Hoffmann-La Roche, is active against DENV in cultured cells.…”
mentioning
confidence: 99%
“…Active siteÀdirected tetrapeptide and tripeptide inhibitors were synthesized to probe the dynamics of the DENV protease active site with different functional groups that compete with the substrate. These active site serine-trap inhibitors contained either boronic acid, trifluoromethylketone, or aldehyde as the electrophilic warhead (Schuller et al, 2011) and showed potent protease inhibitor activity against DENV-1À4 NS2B/NS3 protease as well as other flaviviral proteases, thus demonstrating that pan-dengue or pan-flaviviral protease inhibitors can be developed (Chu et al, 2015;Dwivedi et al, 2016;Pelliccia et al, 2017;Soares et al, 2018;Tan et al, 2018;Wu et al, 2015). In addition to targeting polyprotein processing, it has been shown that specific translational inhibitors can be developed.…”
Section: Polyprotein Processing and Translation Inhibitorsmentioning
confidence: 99%